Does Economics and Business Education Wash Away Moral Judgment Competence? - Hummel, Katrin (Journal of business ethics, 2018)
In view of the numerous accounting and corporate scandals associated with various forms of moral misconduct and the recent financial crisis, economics and business programs are often accused of actively contributing to the amoral decision making of their graduates. It is argued that theories and ideas taught at universities engender moral misbehavior among some managers, as these theories mainly focus on the primacy of profit-maximization and typically neglect the ethical and moral dimensions of decision making. To investigate this criticism, two overlapping effects must be disentangled: the self-selection effect and the treatment effect. Drawing on the concept of moral judgment competence, we empirically examine this question with a sample of 1773 bachelor’s and 501 master’s students. Our results reveal that there is neither a self-selection nor a treatment effect for economics and business studies. Moreover, our results indicate that—regardless of the course of studies—university education in general does not seem to foster students’ moral development.